2010
DOI: 10.1523/jneurosci.1042-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus-1 Tat Activates Calpain Proteases via the Ryanodine Receptor to Enhance Surface Dopamine Transporter Levels and Increase Transporter-Specific Uptake andVmax

Abstract: Human immunodeficiency virus-associated neurological disease (HAND) still causes significant morbidity, despite success reducing viral loads with combination antiretroviral therapy. The dopamine (DA) system is particularly vulnerable in HAND. We hypothesize that early, "reversible" DAergic synaptic dysfunction occurs long before DAergic neuron loss. As such, aging human immunodeficiency virus (HIV)-infected individuals may be vulnerable to other age-related neurodegenerative diseases like Parkinson's disease (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 104 publications
(162 reference statements)
2
51
4
Order By: Relevance
“…In DRG neurons, the increased excitability may partly result from an inhibition of Cdk5, although the concentration of Tat used (20 M) was much higher than used in our present study (100 nM). The 100 nM concentration was chosen for our studies from a range that elicited functional deficits in glia and neurons similar to those occurring in HIV-1 and that are considered to reflect levels seen under pathological conditions (Kruman et al, 1998;Nath et al, 1999;El-Hage et al, 2005Perry et al, 2010). In enteric neurons, we found that increased excitability is seen within 15 min and remains when examined in Tat transgenic mice following induction of the gene for over 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…In DRG neurons, the increased excitability may partly result from an inhibition of Cdk5, although the concentration of Tat used (20 M) was much higher than used in our present study (100 nM). The 100 nM concentration was chosen for our studies from a range that elicited functional deficits in glia and neurons similar to those occurring in HIV-1 and that are considered to reflect levels seen under pathological conditions (Kruman et al, 1998;Nath et al, 1999;El-Hage et al, 2005Perry et al, 2010). In enteric neurons, we found that increased excitability is seen within 15 min and remains when examined in Tat transgenic mice following induction of the gene for over 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Tat increases [Ca 2+ ] in by inducing Ca 2+ influx through Ca 2+ -permeable ion channels and release of intracellular Ca 2+ stores [49, 5254]. This review seeks to summarize what is currently known about (i) Tat-mediated increases of Ca 2+ influx in neurons (mediated mainly by NMDAR, the L-channel and TRPC channel), (ii) Tat-mediated changes in intracellular Ca 2+ release, and (iii) the functional interplay of these channels, which could also be altered by Tat.…”
Section: Tat-mediated Dysregulation Of Ca2+ Influx and [Ca2+]in: Mmentioning
confidence: 99%
“…Third, Tat mediates increase of GSK-3β activity in rat cerebellar granule neurons [78] and midbrain primary neurons [54], and decrease of β-catenin activity in astrocytes [79, 80]. These changes are also associated with abnormal increases of [Ca 2+ ] in .…”
Section: Tat-mediated Dysregulation Of Ca2+ Influx and [Ca2+]in: Mmentioning
confidence: 99%
See 1 more Smart Citation
“…The DAT is reduced in HIV patients, especially in those with cognitive/motor deficits [88]; DAT deficits correlate with cognitive/motor impairments [89]. As reported in our own and others work, DAT is directly targeted by HIV-1 proteins resulting in transporter impairment [9197]. …”
Section: Pediatric Hiv/aids Infectionmentioning
confidence: 96%